A Marxist Reading of Little Fires Everywhere (2017) By Celeste Ng - Dwi Mayang Sagita; Delvi Wahyuni (English Language and Literature, 2020)
This thesis is an analysis of a novel written by Celeste Ng entitled Little Fires Everywhere (2017). This analysis looks at the commodification and alienation that is experienced by women who involved in surrogacy and adoption. This analysis employes Marxist literary theory to explain the phenomena in the novel. The analysis focuses on two issues of commodification and alienation that are proposed by Karl Marx as seen through two female protagonists which are Mia Warren and Bebe Chow. This analysis also depends a lot on the narrator to determine which parts of the novel are used as the data. The result of the study shows that Mia Warren experienced commodification of the human body and four kinds of alienation such as alienation from the product of labor, alienation from the act of production, alienation from the species being, and alienation from other people bacause she becomes a surrogate mother. The other protagonist, Bebe Chow, also experienced four kinds of alienation because her child is adopted.